Performing Compression and Encryption Simultaneously in Data Transmission (Journal of the College of Basic Education, 2022)
The main goals of this paper is to preserve data confidentiality, integrity and reduce the redundancy in data representation when transmitting data across a public computer network. The basic of this research is to develop a method for combining the operation of compression and encryption on the same set of data to perform these two operations simultaneously instead of separately. This is achieved through embedding encryption into compression algorithms since both cryptographic ciphers and entropy coders bear certain resemblance in the sense of secrecy. The proposed system is implemented using Microsoft visual C#.NET programming language.